The Impact of Digital Transformation on Organisational Performance in UAE Construction Organisations: The Moderating Role of Organisational Culture - SHATAT, BASHAR KHALID (2025)
This study investigates the influence of Digital Transformation (DT) on Organisational Performance (OP) in UAE construction organisations, moderated by Organisational Culture (OC). Despite national strategies like UAE Vision 2030, the construction sector remains hesitant to embrace DT or translate digital investments into measurable performance gains. Addressing this gap, the study assesses current DT maturity, its direct impact on OP, and the moderating effect of OC. Adopting a positivist, quantitative, deductive, and cross-sectional design, a structured 30-item questionnaire (5-point Likert scale with an optional final open-ended question) was distributed to professionals across diverse roles, organisation types and sizes, yielding 81 valid responses (from 86 surveyed professionals). Data were analysed using SPSS and Excel using descriptive statistics, ANOVA, Cronbach’s Alpha, Pearson’s correlation, and regression and moderation analyses. Findings revealed moderate-to-high DT maturity, with strong adoption of BIM and cloud technologies but limited use of IoT and AI. Sectoral resistance (notably in infrastructure) and size-based variations in OC were also observed. Regression analysis showed DT accounted for 54.6% of the variance in OP (supporting H1), while moderation analysis revealed a significant but negative interaction effect (rejecting H2), indicating that stronger OC may hinder DT benefits unless strategically aligned. The study contributes to the TOE and IBV frameworks by highlighting the critical role of a cultural alignment—rather than strength—in enhancing DT outcomes. Practical implications include developing a Cultural Alignment Index and UAE-specific, sectoral DT frameworks. Limitations include a small sample size and reliance on self-reported data. Future research should adopt longitudinal or mixed methods and explore cross-GCC comparisons.